1996
DOI: 10.1002/(sici)1097-0215(19960117)65:2<192::aid-ijc11>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Lu-ECAM-1-mediated adhesion of melanoma cells to endothelium under conditions of flow

Abstract: Metastasis is thc proccss hy which primary cancer cclls establish new tumor colonies in select, secondary organ sites.Selection of a target organ for metastasis occurs in nonrandom fashion and is dictated by compatible tumor-cell and host-cell characteristics. A primary step in this selection process is adhesion of blood-borne tumor cells to distinct, organ-specific adhesion molecules, constitutively expressed on the luniinal surface of endothelial cells of the target site (reviewed by Albclda, 1993; Lafrcnic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Because all lung-metastatic cancer cells tested in our laboratory, including MDA-MB-231, B16-F10, 4T1, MTF7, LLC1, and K7M2, exhibit high message and protein levels for both FN and integrin ␤ 4 and adhere to both of the respective pulmonary addressins (DPPIV and CLCA), it is conceivable that pulmonary vascular arrest of blood-borne cancer cells is initiated by the DPPIV/poly-FN adhesion and is stabilized by the CLCA/ integrin ␤ 4 adhesion discovered in this laboratory (42,56). Circumstantial support for this notion came from studies of the CLCA/integrin ␤ 4 adhesion under flow conditions (57). These experiments showed that integrin ␤ 4 -expressing tumor cells adhere to CLCA-coated dishes only at low shear stresses.…”
Section: Discussionmentioning
confidence: 93%
“…Because all lung-metastatic cancer cells tested in our laboratory, including MDA-MB-231, B16-F10, 4T1, MTF7, LLC1, and K7M2, exhibit high message and protein levels for both FN and integrin ␤ 4 and adhere to both of the respective pulmonary addressins (DPPIV and CLCA), it is conceivable that pulmonary vascular arrest of blood-borne cancer cells is initiated by the DPPIV/poly-FN adhesion and is stabilized by the CLCA/ integrin ␤ 4 adhesion discovered in this laboratory (42,56). Circumstantial support for this notion came from studies of the CLCA/integrin ␤ 4 adhesion under flow conditions (57). These experiments showed that integrin ␤ 4 -expressing tumor cells adhere to CLCA-coated dishes only at low shear stresses.…”
Section: Discussionmentioning
confidence: 93%
“…The bCLCA2 (Lu-ECAM-1) ortholog was cloned using antibody that blocked the adhesion-receptor/ligand pair that mediates binding of lung metastatic melanoma cells to bovine aortic endothelial cells (50,70,212,214). The origins of the clone identify bCLCA2 as the endothelial adhesion molecule that binds hematogeneous tumor cells, causing vascular arrest before tumor growth and invasion.…”
Section: Clca and Cell Adhesionmentioning
confidence: 99%
“…11). The purified molecule promotes strong adhesion of B16-F10 cells under static and hydrodynamic conditions (14) and, in soluble form, competi-tively inhibits adhesion of these tumor cells to immobilized Lu-ECAM-1 (11,13). Here, we identify other components of the Lu-ECAM-1 complex and define their interrelationships.…”
mentioning
confidence: 94%